The Assosiation Between Nutritional Status and Fine Motor Development in Children Aged 36-42 Months - Wari, Fitria Edni; Yuliani, Farida; Mail, Erfiani (Jurnal Midpro, 2022)
Motor development is related to nutritional status, optimal nutrition affects the physical growth of cell proliferation. Malnutrition will affect the development of children where the proportion of body structure becomes inappropriate for their age and interferes with the development of other aspects, one of which is fine motor development. This study used an analytical survey research design with a cross sectional approach with the aim of knowing the relationship between nutritional status and fine motor development. The population and sample in this study were 36-42 months old children in PAUD Tarbiyatush Shibyan, Gayaman Village, Mojoanyar District, amounting to 36 children with a total sampling technique. This study uses a weight scale instrument to measure body weight in determining the nutritional status of children with the criteria of Weight based on Age and KPSP (Kuesioner Pra Skrining Perkembangan) observation sheet to measure children's fine motor development. Data analysis with univariate analysis and bivariate analysis on two variables that are suspected to be correlated. Chi Square test was performed. Chi Square test results obtained p Value = 0.004 <0.05 which indicates that there is a relationship between nutritional status and fine motor development in PAUD Tarbiyatush Shibyan, Gayaman Village, Mojoanyar District. Midwife coordinates with the teaching staff/teachers in the school to monitor progress and continuous stimulation.